2020
DOI: 10.1111/nyas.14489
|View full text |Cite
|
Sign up to set email alerts
|

Spherization of red blood cells and platelet margination in COPD patients

Abstract: Red blood cells (RBCs) in pathological situations undergo biochemical and conformational changes, leading to alterations in rheology involved in cardiovascular events. The shape of RBCs in volunteers and stable and exacerbated chronic obstructive pulmonary disease (COPD) patients was analyzed. The effects of RBC spherization on platelet transport (displacement in the flow field caused by their interaction with RBCs) were studied in vitro and by numerical simulations. RBC spherization was observed in COPD patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In bio-fluid simulation, by integrating immersed boundary method (IBM), Palabos has been used to simulate blood cell movement and deformation in plasma flow, that is a frontier research focus of hemodynamic simulation. 29,30 The listed demo-examples of Palabos include haemodynamic simulation of an intracranial aneurysm. As the vessel dimensions of intracranial vessels and coronary vessels are similar, the simulations in this study maintain the most settings as the demo-example of aneurysm.…”
Section: Lbm Methodsmentioning
confidence: 99%
“…In bio-fluid simulation, by integrating immersed boundary method (IBM), Palabos has been used to simulate blood cell movement and deformation in plasma flow, that is a frontier research focus of hemodynamic simulation. 29,30 The listed demo-examples of Palabos include haemodynamic simulation of an intracranial aneurysm. As the vessel dimensions of intracranial vessels and coronary vessels are similar, the simulations in this study maintain the most settings as the demo-example of aneurysm.…”
Section: Lbm Methodsmentioning
confidence: 99%
“…The numerical simulations provide one explanation of the experimental results obtained, indicating that the RBC spherization causes an increase in platelet transport to the wall, which. [Zouaoui Boudjeltia et al, 2020]. This indicates that the changes of RBC shapes affect platelets transport and thus the platelets properties of adhesion and aggregation to the wall.…”
Section: Discriminating Parametersmentioning
confidence: 96%
“…Furthermore, in pathological situations, RBCs may undergo biochemical and conformational changes, altering blood rheology [Bujak et al, 2015]. Spherization of RBCs has been demonstrated in sepsis, dialysis patients, COPD patients and other pathologies causing chronic or acute systemic inflammation [Piagnerelli et al, 2007, Zouaoui Boudjeltia et al, 2020. Recently, we reported that the RBC spherization induces an increase in platelet adhesion and aggregation processes.…”
Section: Discriminating Parametersmentioning
confidence: 99%
“…Figure 9 presents a closer look to some critical Grasshopper components. The generation of RBC/PLT meshes can be done either in Rhino-Grasshopper (and any other CAD software), or through scripts using formulas to generate the investigated surfaces [4].…”
Section: Rhino-grasshopper Environment For Setting Up New Materialsmentioning
confidence: 99%
“…Given the cellular nature of blood, its rheology can be deciphered by understanding how the various cells are moving and interacting with each other in both healthy and non-healthy humans. Numerical tools have significantly assisted in in-depth investigations of blood rheology, as they offer a controlled environment for testing a large number of parameters and classifying their effect [4,8]. Furthermore, the amount of detail coming from the numerical simulations at the microscopic level (following individual cells) is unparalleled compared to the in-vitro/in-vivo counterparts.…”
mentioning
confidence: 99%